2005
DOI: 10.3354/dao063101
|View full text |Cite
|
Sign up to set email alerts
|

Taura syndrome virus (TSV) in Thailand and its relationship to TSV in China and the Americas

Abstract: The cultivation of exotic Penaeus vannamei in Thailand began on a very limited scale in the late 1990s, but a Thai government ban on the cultivation of P. monodon in freshwater areas in 2000 led many Thai shrimp farmers to shift to cultivation of P. vannamei. Alarmed by the possibility of Taura syndrome virus (TSV) introduction, the Thai Department of Fisheries required that imported stocks of P. vannamei be certified free of TSV by RT-PCR (Reverse Trasciption Polymerase Chain Reaction) testing. During the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 14 publications
0
39
1
2
Order By: Relevance
“…In addition, the Korean peninsula is geographically much closer to Taiwan than to Thailand and thus it is unlikely that the Thailand TSV strain rather than the Taiwan TSV strain would naturally infect shrimp cultured in Korea. Recently, it has been reported that the genotype of Chinese TSV isolates is closely related to TSV isolates from SE Asia (Nielsen et al 2005, Tang & Lightner 2005. This suggests that TSV may be introduced into Korea through illegal importation of P. vannamei from China; however, we currently have no evidence to support this possibility.…”
Section: Previously In Diseases Of Aquatic Organisms (Dao)contrasting
confidence: 45%
“…In addition, the Korean peninsula is geographically much closer to Taiwan than to Thailand and thus it is unlikely that the Thailand TSV strain rather than the Taiwan TSV strain would naturally infect shrimp cultured in Korea. Recently, it has been reported that the genotype of Chinese TSV isolates is closely related to TSV isolates from SE Asia (Nielsen et al 2005, Tang & Lightner 2005. This suggests that TSV may be introduced into Korea through illegal importation of P. vannamei from China; however, we currently have no evidence to support this possibility.…”
Section: Previously In Diseases Of Aquatic Organisms (Dao)contrasting
confidence: 45%
“…First seen in shrimp farms located along the Taura River in Ecuador in 1992, TS spread rapidly to other countries in Central and South America and to Mexico and the United States (Jimenez 1992, Brock 1997. The introduction of P. vannamei culture in Taiwan, China, Thailand and Indonesia also resulted in the spread of TS virus (TSV) to these regions within a relatively short period of time (Tu et al 1999, Yu & Song 2000, Nielsen et al 2005. Several genotypes or strains are now known to exist and the virus remains an important infectious disease in countries where P. vannamei is farmed (Erickson et al 2002, Lien et al 2002, Robles-Sikisaka et al 2002, Rosenberry 2002.…”
Section: Introductionmentioning
confidence: 99%
“…There were 3 distinct phylogenetic lineages in the Americas, Asia, and Belize. Nielsen et al (2005) also reported that TSV isolates from Asia and the Americas were distinct.…”
Section: Introductionmentioning
confidence: 99%
“…There were 3 distinct phylogenetic lineages in the Americas, Asia, and Belize. Nielsen et al (2005) also reported that TSV isolates from Asia and the Americas were distinct.Because TS causes high mortalities in Litopenaeus vannamei (Lightner 1996), scientists have attempted to develop TSV-resistant shrimp populations (Wyban 2000, White et al 2002, Xu et al 2003. This is important because L. vannamei is the predominant cultivated species worldwide (FAO 2004).…”
mentioning
confidence: 99%